Sources of funding for MSMEs in developing countries: Success cases in Africa - Teixeira, N.; Carvalho, L.; Santos, M.; Galvão, R. (Handbook of research on acceleration programs for SMEs, 2023)
Access to financing for micro, small, and medium entrepreneurs continues to face obstacles and difficulties. This scenario becomes even more evident when we refer to the situation of the under-development countries, where the financial system still shows tendencies that do not favor the productive sector. Thus, this chapter begins by identifying the main financing constraints faced by MSMEs in developing countries. In the following sections, and according to several international studies and reports from the world main organizations and financial institutions that support the dynamism of the economies of developing countries, are presented and characterized the sources of capital and financial innovations developed over time, that have allowed a greater integration into the formal financial system of publics such as women, young people, and rural populations. In the last seccion are presented some of success cases in Africa and a reflexion is made about recommendations of funding sources to be implemented, to boost the activity of MSMEs in emergent economies.